2019
DOI: 10.1038/s41598-019-47543-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile Hydrophobication of Glutathione-Protected Gold Nanoclusters and Encapsulation into Poly(lactide-co-glycolide) Nanocarriers

Abstract: We report a simple surface functionalization of glutathione-capped gold nanoclusters by hydrophobic ion pairing with alkylamine followed by a complete phase transfer to various organic solvents with maintained colloidal stability and photoluminescence properties. The described surface hydrophobication enables efficient encapsulation of gold nanoclusters into PLGA nanocarriers allowing their visualization inside cultured cells using confocal fluorescent microscopy. The simplicity and efficiency of the described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Although the NaCl crystal was partially melted under electron beam irradiation, 29 the GSH-Au NCs were still observed in the NaCl matrix. The high-resolved TEM (HRTEM) image (Figure 2b) further shows that the confined GSH-Au NCs present an average diameter of ∼1.2 nm with the lattice fringe of 2.4 Å, attributing to d spacing of the (111) plane of the metallic Au, 30 which is consistent with those of free GSH-Au NCs (Figure S1). Thus, it is believed that the GSH-Au NCs are incorporated into NaCl crystals.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…Although the NaCl crystal was partially melted under electron beam irradiation, 29 the GSH-Au NCs were still observed in the NaCl matrix. The high-resolved TEM (HRTEM) image (Figure 2b) further shows that the confined GSH-Au NCs present an average diameter of ∼1.2 nm with the lattice fringe of 2.4 Å, attributing to d spacing of the (111) plane of the metallic Au, 30 which is consistent with those of free GSH-Au NCs (Figure S1). Thus, it is believed that the GSH-Au NCs are incorporated into NaCl crystals.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…55 Due to the high sensitivity toward reactive oxygen species (ROS), the Oxi-Dex shell dissociated in the presence of H 2 O 2 , accompanied by the release of encapsulated nanoclusters and the recovery of quenched fluorescence. Similarly, by taking advantage of the hydrophobic effect, Alkilany et al 56 reported that hydrophobic GSH–AuNCs, with colloidal stability and photoluminescence properties in various organic solvents, were encapsulated into poly(lactide- co -glycolide) (PLGA) nanocarriers, and taken up by cells.…”
Section: Preparation Strategies Of Aunc Compositesmentioning
confidence: 99%
“…However, various encapsulation approaches may result in very different outcomes. We found that the encapsulation of PLGA-capped GNP into PLGA nanoparticles resulted in higher encapsulation efficiencies when the emulsion-evaporation method was employed compared to nanoprecipitation [ 28 , 60 ]. Luque-Michel et al compared various emulsion-evaporation methods to encapsulate GNP into PLGA carriers and reported the important effects in regards to type of GNP (hydrophilic, hydrophobic) used, the used method (encapsulation pre-formed versus in situ-formed GNP), type of emulsion ( w / o , w / o / w ) and type of emulsifying agent on the encapsulation process [ 61 ].…”
Section: Encapsulation Approaches and Surface Functionalization Of Go...mentioning
confidence: 99%